Auto-antibodies to post-translationally modified proteins in osteoarthritis. Issue 6 (June 2021) - Xie, X.; van Delft, M.A.M.; Shuweihdi, F.; Kingsbury, S.R.; Trouw, L.A.; Doody, G.M.; Conaghan, P.G.; Ponchel, F.
Summary: Objective: Autoantibodies (AutoAbs) have been observed in osteoarthritis (OA) with broad antigenicity, although their prevalence and role remain unclear. Post-translational modification (PTMs) of proteins (oxidation, carbamylation, citrullination) is associated with synovitis and can lead to AutoAb development. Given the prevalence of synovitis, we explored whether AutoAbs to PTM-antigens are common in OA compared with rheumatoid arthritis (RA). Methods: Serum ( n  = 895) was obtained from healthy controls, OA and RA patients; and arthritic synovial fluid (SF, n  = 290). ELISAs were used to quantify anti-citrullinated peptide (ACPA), anti-carbamylated protein (anti-CarP), anti-oxidized collagen (anti-ROS-CI/CII) antibodies. Results: In sera, positivity for PTM-antigens AutoAbs was observed at a lower frequency in OA with 64.1% (95%CI: 57.2–70.1%) more ACPA+ and 29.8% (21.0–37.3%) more anti-CarP + patients in RA (both P  < 0.0001). Levels of ACPA, anti-CarP were also lower in OA ( P  < 0.0001). Anti-ROS-CII positivity was lower in OA compared to RA (16.6%, 4.8–28.6%) less frequent, P  = 0.033) but not anti-native-CII. There was no impact of age/gender on AutoAbs associations with diseases either looking at positivity or levels. In SF, OA patients were often ACPA+ (45.9%) although less frequently than in RA ( P  = 0.004). Anti-CarP were rarely observed (<5% all samples). All collagen AutoAbs were more frequent in RA compared to OA (all P  < 0.010) but only levels of anti-CII and anti-ROS-CII were significantly higher in they RA ( P  < 0.050). Conclusion: Although the frequency of AutoAbs for PTM proteins were lower in OA sera compared to RA, a higher proportion of OA SF were positive. The relative retention of AutoAbs in the OA joint requires further investigation.